Beyond pink collars: Gender, work and family in businesswomen’s narratives - Jaime, Pedro (2011)
The statistics on gender and work in Brazil make evident that, despite the hurdles, women have been able obtain management positions in the business world. However, they still concentrate in the “feminine ghetto”. They work mainly in economic sectors related to social, cultural and health services; earning lower salaries than their male peers. In this article, I present narratives of businesswomen who developed professional trajectories in sectors that are traditionally occupied by men and are elaborated symbolically as masculine. On the basis of this textual corpus I converse with classical arguments and new debates in the field of gender studies.